The Problematic of gender between Islamic thought and Islamic Feminism - Arroussi, Walid; Berradjel, Ihsene (Social Empowerment Journal, 2025)
Feminism is a social movement that emerged to correct the status of women in European society after the French Revolution of 1789. It reflects the social and intellectual conditions European societies had reached at that time, which pushed this broad segment (women) to demand rights they considered denied, and gender equality that feminists saw as essential for the stability and progress of European society. The feminist movement adopted the term gender, which was originally used to describe the sexual orientation of individuals with intersex traits—who constitute a tiny minority in society. Feminism then generalized the term to include individuals with deviant sexual orientations, in an attempt to legitimize these deviations and to create a new space in which such behaviours are accepted and granted legitimacy, rather than being described as deviant. Feminist thought did not emerge from the writings of a single philosopher or thinker; instead, it developed through successive waves that exploited global conditions in each phase. It subsided during crises and wars and intensified during peace and stability. New figures emerged with each wave, along with books and new terms that shaped feminist thought, until it reached its current form. Feminist ideology cannot be considered independent in and of itself; it is a social movement that adopts the intellectual colour of the society in which it operates. Thus, we find liberal feminism, Marxist feminism, and others, including Islamic feminism, which echo the global feminist movement. It raises the same demands and calls for the same rights, despite the fundamental differences between Islamic societies and the European context in which feminism originated. What is acceptable in European society may not be acceptable elsewhere. Furthermore, while religion was sidelined in Europe in favour of secularism, it remains a foundational pillar of Islamic societies and cannot be easily abandoned. The existence of differences between Islamic thought and feminist ideology is inevitable. However, these differences are so deep and fundamental that reconciling Islam and feminist thought seems nearly impossible. Highlighting the depth of these differences is enough to expose interpretive Islamic feminism and present it for what it truly is: a movement in opposition to religion, despite its concealment behind religious texts and its attempt to interpret them through a feminist lens—an approach that contradicts the established jurisprudential, linguistic, and scholarly principles that Islamic scholars have practiced since the dawn of Islam. The idea of making the scholar’s gender a criterion for accepting their scholarly opinion is unprecedented in the Islamic tradition since the revelation began to our Prophet Muhammad, peace be upon him.